Photocatalytic degradation of organic contaminants in water: Process optimization and degradation pathways - Antoniou, Maria G.; Zhao, Cen; O'Shea, Kevin E.; Zhang, Geshan; Dionysiou, Dionysios D.; Zhao, Chun; Han, Changseok; Nadagouda, Mallikarjuna N.; Choi, Hyeok; Fotiou, Theodora; Triantis, Theodoros M.; Hiskia, Anastasia (My University, 2016)
This chapter discusses thoroughly the outcomes of the TiO2 photocatalytic degradation of organic contaminants of emerging concern, including manmade (insecticides, organochlorinated compounds, and antibiotics) and naturally occurring compounds (cyanotoxins and taste and odor compounds). Specifically, information is provided on the degradation of various organic contaminants in actual water samples, their corresponding reaction kinetics, the individual effects of water quality parameters (including pH, natural organic matter, and alkalinity) and nano-interfacial adsorption phenomena. Emphasis is given to the mechanisms of photocatalytic degradation of organic contaminants based on their structural differences and the corresponding transformation products formed.
Keywords: Photoelectrochemical splitting of water; Radiolytic oxidations; Natural organic matter